When change reiterates the norm: curriculum restructuring of medicine in possible connections with sexuality and gender - André Filipe dos Santos Leite; Thiago Ranniery Moreira de Oliveira (Universidade Estadual Paulista Júlio de Mesquita Filho, 2014)
The scenario of medical education has expressed demands and specific configurations, which negotiate a reconfiguration of the ways and means to see and do Medicine, standing in the foreground, a restructuring of medical curricula. In this article, from observations and official documents of a medical curriculum that undergoes restructuring, it is argued that discourses of Sexuality and Gender crossing ways of teaching, learning, doing and practicing medicine in both the model that is considered necessary overcome, as in the model that aims to establish. From a line of action inspired by the analytical of the discourse of Michel Foucault, the aim is to show how the medical discourse is gendered and sexualized, and as the Medical produces gender and sexualizes bodies through the medicalization understood as moralizing of sexuality. Finally, as has worked in management, marking, cataloging, standardizing, normalizing, standardizing, and pathologizing medicalizando bodies.